Analisis Pemungutan Ulang Surat Suara Pemilu Tahun 2019 di Dusun Bakalan Desa Argomulyo Kecamatan Cangkringan Kabupaten Sleman - Widiastuti, Ari; Handoko , Sigit (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the 2019 election ballots in Bakalan Village, Argomulyo Hamlet, Cangkringan District, Sleman Regency, Yogyakarta. This research is a research with qualitative descriptive techniques and the method used is analysis. Data collection techniques were in the form of interviews, observation, and documentation. The researcher went directly to the research site to find out the data written in the Bakalan and interviewed the source directly to obtain accurate data. Data obtained in the field were analyzed descriptively qualitatively. The research results are concluded as follows: (1). Re-voting (PSU) at TPS 03 Bakalan, Argomulyo Village, Cangkringan District, Sleman Regency was held because there were 2 migrant residents who did not carry A5 letters. This is in accordance with Law Number 7 of 2017 concerning General Elections article 372 paragraph (2). PSU is carried out on the recommendation of Bawaslu. (2) Re-voting (PSU) at TPS 03 Bakalan, Argomulyo Village, Cangkringan District, Sleman Regency is in accordance with Law Number 7 of 2017 Article 373 paragraph (3) and Article 66 paragraph (3) KPU Regulation No. 3 of 2017 2019, namely re-voting at TPS is carried out no later than 10 (ten) days after voting day. PSU was held on April 24 2019. (3). The re-voting at TPS 03 Argomulyo Cangkringan was attended by 146 DPTb. There are 146 voters who use their right to vote.